A QUANTITATIVE PERFORMANCE MANAGEMENT FRAMEWORK TO IMPROVE COMMUNITY ECONOMY THROUGH OMNICHANNEL SUPPLY CHAIN: A CASE STUDY IN THE BANKING AND MARKETING INDUSTRY - Zaenal Aripin; Farida Yulianty; Fitriana (KRIEZ ACADEMY : Journal of development and community service, 2023)
In the era of digital transformation, the Quantitative Performance Management Framework (QPMF) has emerged as a potential solution to increase operational efficiency and the industrial sector's contribution to society's economic growth. This study explores the application of KM2K in the context of omnichannel supply chains, with a focus on the banking and marketing industries. This research aims to investigate the impact of implementing QPMF in improving the community's economy through an omnichannel supply chain, with special emphasis on its role in the banking and marketing industries. This research uses a Systematic Literature Review (SLR) approach to compile and analyze related literature. In addition, case studies are used to understand the application of QPMF in the real context of the banking and marketing industry. Data was collected through interviews, observation and documentation analysis to gain in-depth insight. The research results show that the application of QPMF in the banking industry makes a significant contribution to operational efficiency, strategic decision making, and responsibility to customer needs through an omnichannel supply chain. In the marketing sector, QPMF enables optimization of marketing strategies, personalization of campaigns and increased responsiveness to market trends.